New Headway. Elementary: Student's Book - Soars L. Liz (Oxford, Oxford University Press, 2006)
New Headway ElementaryThe world's most trusted English course New Headway is the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written.What's different about the THIRD edition of New Headway Elementary? NEW Up-to-date texts and topicsNEW Integrated writing syllabus and pairwork activitiesNEW Music of English boxes focus on stress and intonation in Everyday English NEW Integrated practice exercises in the Grammar Reference NEW Fresh, new design. Attractive, well-organised, and easy to use.